Cultivation of Flammulina velutipes mushroom using various agro‑residues as a fruiting substrate - Harith, Nooraishah; Abdullah, Noorlidah; Sabaratnam, Vikineswary (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the feasibility of different agro‑residues as a carbon source in the fruiting substrates of Flammulina velutipes mushroom and the effect of supplementation with the nitrogen sources spent brewer’s yeast and rice bran. The following fruiting substrates were evaluated: rubber wood sawdust (SD), paddy straw (PS), palm empty fruit bunches (EFB), and palm‑pressed fiber (PPF). Cultivation was done on each agro‑residue, based on formulations consisting of two substrates at the ratios of 3:1, 1:1, and 1:3. Mycelial growth rate and basidiocarp yield were evaluated. The best fruiting substrates were PS+EFB (25:75), PS+PPF (50:50), and PPF (100), with biological efficiency of 185.09±36.98, 150.89±50.35, and 129.06±14.51%, respectively. No significant effects of supplementation with rice bran and spent yeast were observed on mycelial growth rate and biological efficiency. The cultivation of F. velutipes on oil palm wastes does not require additional nitrogen sources.